2015
DOI: 10.3748/wjg.v21.i10.3020
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines levels are associated with the severity of liver disease in patients with alcoholic cirrhosis

Abstract: Adipokines are associated with deteriorating liver function in a complex manner in patients with alcoholic liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 55 publications
0
27
1
Order By: Relevance
“…Increased systemic adiponectin in the cirrhotic patients has been identified in all of the studies ( Table 1 ) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Importantly, elevated adiponectin is found in the patients independent of disease etiology ( Table 1 ) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Higher adiponectin was identified in normal-weight and overweight patients independent of the age of the participants in each cohort ( Table 1 ).…”
Section: Adipokines In Liver Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…Increased systemic adiponectin in the cirrhotic patients has been identified in all of the studies ( Table 1 ) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Importantly, elevated adiponectin is found in the patients independent of disease etiology ( Table 1 ) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Higher adiponectin was identified in normal-weight and overweight patients independent of the age of the participants in each cohort ( Table 1 ).…”
Section: Adipokines In Liver Cirrhosismentioning
confidence: 99%
“…Higher adiponectin was identified in normal-weight and overweight patients independent of the age of the participants in each cohort ( Table 1 ). Interestingly, there are no associations of serum adiponectin with the homeostasis model assessment (HOMA) index, as a surrogate marker of insulin sensitivity [ 59 , 61 ] or body mass index (BMI) [ 63 , 65 ] in cirrhosis patients. High adiponectin even increases the risk to develop hepatocellular carcinoma in HCV-infected patients [ 66 ] suggesting that the well-characterized hepatoprotective and anti-carcinogenic effects of this adipokine are blocked [ 2 , 67 ].…”
Section: Adipokines In Liver Cirrhosismentioning
confidence: 99%
“…Serum apelin levels were decreased in patients with cardiac, renal, and pulmonary fibrosis and PAH . In contrast, serum apelin levels were elevated in patients with liver fibrosis . In this study, we determined that serum apelin levels were negatively correlated with skin sclerosis in SSc patients, which suggests that decreased serum apelin levels might be associated with skin fibrosis in SSc.…”
Section: Discussionmentioning
confidence: 74%
“…Another recent study [6] reported that in subjects with alcoholic cirrhosis following adjustment for fat mass, visfatin levels were significantly higher from Child-Pugh Class A to Class C.…”
Section: Introductionmentioning
confidence: 99%